{Cercospora sp. as a source of anti-aging polyketides targeting 26S proteasome and scale-up production in submerged bioreactor} - Georgousaki, Katerina; Tsafantakis, Nikolaos; Gumeni, Sentiljana; González-Menéndez, Victor; de Pedro, Nuria; Tormo, José Rubén; Almeida, Celso; Lambert, Carole; Genilloud, Olga; Trougakos, Ioannis P.; Fokialakis, Nikolas (Journal of Biotechnology, 2019)
From a large screening of microbial extracts for the discovery of proteasome modulating natural products, the fungal strain Cercospora sp. (CF-223709) was selected as the most promising for further investigation. Different liquid cultures of the strain were initially screened for their anti-oxidant activity (DPPH, ABTS) and for their cytotoxicity against the A2058, HepG2 and CCD25sk cell lines. A detailed chemical analysis and evaluation of the capacity to activate 26S-proteasome was followed for the most active extract. Three main polyketides were isolated and characterized by extensive analysis of NMR and HRMS spectra data as penialidine F (1), fulvic acid (2), and SB238569 (3). Fulvic acid showed the most significant anti-oxidant activity. Its IC50 value (8.16 $μ$M) against the ABTS radical resulted 3-fold lower than the standard trolox. Fulvic acid also demonstrated a significant effect on proteasome by enhancing the chymotrypsin- and caspase-like activities of the 26S proteasome of human fibroblasts by 71.43{%} and 37.5{%} at 1 $μ$M, respectively. Furthermore by scaling up the culture in a 30 L submerged bioreactor, Cercospora sp. produced up to 162.6 ± 1.3 mg of fulvic acid/L. Our findings suggest that CF-223709 can be a promising source of proteasome activating natural compounds.
Keywords: Antioxidant activity; Bioreactor; Cercospora; Filamentous fungi; Polyketides; Proteasome